Uji Aktivitas Anti Hiperurisemia Ekstrak n-Heksana, Etil Asetat, dan Etanol 70% Biji Jinten Hitam (Nigella sativa) terhadap Mencit Hiperurisemia (Anti Hyperuricemic activity of n-Hexane, Ethyl acetate, and Ethanol 70% of Black Cumin Seed (Nigella sativa) - Umar Dian Prambudi Kusuma; Siti Muslichah; Evi Umayah Ulfa (Pustaka Kesehatan, 2014)
The aim of this study was to determine the in vivo anti-hyperuricemic effect of black cumin extract. Black cumin was extracted with n-hexane, ethyl acetate, and ethanol 70% continously. Fifteen mice were divided into five groups K-, K+, P1, P2, and P3. Group K- as negative control (chicken liver juice 0,2 % b/v) and group K+ as positive control (allopurinol 10 mg/kg b.w.). Group P1, P2, and P3 received n-hexane, ethyl acetate, and ethanol 70% black cumin extract. The extracts were given to mice in 200 mg/kg b.w dose for 4 days. The blood samples were taken an hour after potassium oxonate injection (300 mg/kg b.w) to inhibit uricase enzym. The data was collected and analyzed using one way ANOVA and LSD test. The result showed that activity of ethyl acetate extract of black cumin has no significant difference of possitive control. Based on phytochemistry screening it has terpenoid, saponin, and alkaoid. Terpenoid has anti-hyperuricemic effect but its mechanism still unknown.   Keywords: hyperuricemic, Nigella sativa, terpenoid.